Appendix D: Theophorous names based on the divine name Ḫaldi attested in Neo-Assyrian and Achaemenid-period cuneiform sources - Grekyan, Yervand (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
Theophorous names based on the divine name Ḫaldi attested in Neo-Assyrian and Achaemenid-period cuneiform sources.